2017
DOI: 10.1097/ncc.0000000000000399
|View full text |Cite
|
Sign up to set email alerts
|

“I Had a Little Bit of a Bloke Meltdown…But the Next Day, I Was Up”

Abstract: Aboriginal men could be better engaged with cancer diagnosis and treatment if greater attention was paid to recognizing preferred approaches, including pragmatism and humor, and supporting connections to family and culture throughout the cancer journey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…After removing duplicate studies, the titles and abstracts of 543 studies were screened, with 59 studies identified for full-text screening. Twenty-three qualitative studies [ 18 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] were included in the review after excluding quantitative studies ( n = 16), studies using the same dataset with different aims ( n = 3), studies not focused on Indigenous people’s experience with cancer ( n = 7), and studies not focused on Indigenous people with cancer ( n = 10).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After removing duplicate studies, the titles and abstracts of 543 studies were screened, with 59 studies identified for full-text screening. Twenty-three qualitative studies [ 18 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] were included in the review after excluding quantitative studies ( n = 16), studies using the same dataset with different aims ( n = 3), studies not focused on Indigenous people’s experience with cancer ( n = 7), and studies not focused on Indigenous people with cancer ( n = 10).…”
Section: Resultsmentioning
confidence: 99%
“…At least 145 participants (60%) were from regional/rural or disadvantaged areas. Ten studies had the same participants who shared their experiences in different healthcare service areas living in Northern Territory ( n = 3) [ 24 , 25 , 26 ], New South Wales ( n = 2) [ 29 , 38 ], and Western Australia ( n = 5) [ 33 , 34 , 35 , 36 , 39 ]. Most of the studies ( n = 21) conducted state-wide research; only two were conducted at the national level [ 21 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations